2013
DOI: 10.1371/journal.pone.0080333
|View full text |Cite
|
Sign up to set email alerts
|

Family History as a Predictor for Disease Risk in Healthy Individuals: A Cross-Sectional Study in Slovenia

Abstract: BackgroundFamily history can be used as a genetic risk predictor for common non-communicable diseases. The aim of this study was to determine the prevalence of healthy individuals at risk of developing these diseases, based on their self-reported family history.Methods and FindingsThis was a cross-sectional observational study. Data were collected in the three largest occupational practices in primary health care centres in Slovenia, a Central European country. The study population consisted of consecutive ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Although the term “family history of CVD (or CHD)” is frequently used, there is no common or uniform definition at the moment. Most definitions include statements of either “family history of CVD” or “family history of CVD (or CHD, or stroke, or heart attack) among first-degree relatives” and are treated as a binary variable [ 21 , 22 ]. The current most common definition of family history of CVD also includes the age of CVD occurrence: early (premature) CVD (at age before 55 or 60 years for men and before 65 years for women) and late CVD in first-degree relatives [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the term “family history of CVD (or CHD)” is frequently used, there is no common or uniform definition at the moment. Most definitions include statements of either “family history of CVD” or “family history of CVD (or CHD, or stroke, or heart attack) among first-degree relatives” and are treated as a binary variable [ 21 , 22 ]. The current most common definition of family history of CVD also includes the age of CVD occurrence: early (premature) CVD (at age before 55 or 60 years for men and before 65 years for women) and late CVD in first-degree relatives [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, the results of cross-sectional and prospective studies show that from 6.5% to 50% of respondents have a first or second-degree relative with CVD [ 7 , 8 , 22 , 27 , 28 ]. The differences in the prevalence of family history of CVD found in epidemiological studies might be explained by the differences in study samples (age, gender, disease status (free from CVD or with CVD at baseline)) and different definitions of the family history of CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Qureshi, a systematic consideration of positive family burden with CVD showed that there were 4.8% more patients at high risk of CVD (13). An FH of diabetes is associated with an increased risk of developing the condition (14,15). This risk can be assessed in the general population, and using FH in cancer patients can identify families at increased risk of malignant diseases (16).…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported family history within a sample of 1340 healthy Slovenian respondents found 280 (or 20%) at moderate or high risk for developing CVD, 154 (11.5%) for diabetes, and 163 (12.1%) for cancer, leading to the recommendation to offer genetic evaluation 9. This response aligns with clinical intervention, including genetic testing, while neglecting consideration of whether available and affordable resources for evaluation and follow-up exist.…”
mentioning
confidence: 99%